2017
DOI: 10.1097/md.0000000000007092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multidisciplinary team on emergency care for colorectal cancer patients

Abstract: The literature describing the effectiveness of multidisciplinary team (MDT) for the care of colorectal cancer remains unclear. We investigated the effects of MDT care on the quality of colorectal cancer treatment, and the emergency department visit number was used as an indicator. In total, 45,418 patients newly diagnosed with colorectal cancer from the Taiwan National Health Insurance Research Database (2005–2009) were included. Propensity score matching with a ratio of 1:3 was adopted to reduce differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The control group (non-MDT) included patients who did not receive MDT treatment during the period 2006-2016. Many studies have assessed the effect of MDT meetings [18][19][20][21] and have suggested that patients treated by MDT had A longer survival time than other patients. The effectiveness of an MDT is associated with its organization, process, and the disease being treated.…”
Section: Introductionmentioning
confidence: 99%
“…The control group (non-MDT) included patients who did not receive MDT treatment during the period 2006-2016. Many studies have assessed the effect of MDT meetings [18][19][20][21] and have suggested that patients treated by MDT had A longer survival time than other patients. The effectiveness of an MDT is associated with its organization, process, and the disease being treated.…”
Section: Introductionmentioning
confidence: 99%
“…Early advanced practice nursing involvement in the care of elderly patients with cancer who received surgical intervention improved survival in this group by an average of seven months. As well, the need for emergency care was lower in patients receiving MDT treatment within a year of cancer diagnosis (OR=0.87) [ 23 24 ]. In our study, 65% of the patients had MDT assessment during their stay comprised largely by gastroenterology and interventional radiology.…”
Section: Discussionmentioning
confidence: 99%
“…The need for review of pathology and radiology findings during discussion speaks for the success and importance of these meetings. 2 , 6 , 10 These meetings also serve as a platform for learning. Due to extensive advancement in the field of radiology over the past years, the decisions for making the choice of radiological procedure has become complex now.…”
Section: Discussionmentioning
confidence: 99%